(untitled) (International Journal of Engineering and Computer Science, 2016)
: A mobile ad hoc network (MANET) is a collection of mobile nodes that is joined through wireless medium forming rapidly changing topologies. MANET’s are infrastructure-less and can be set up anytime, anywhere. The survey of protocol properties has been conducted of various MANET routing algorithms and analyzed them. The routing algorithms are categorized into two i.e. proactive (table driven) and reactive (on demand). The algorithms considered are DSDV, DSR, and AODV. The comparison of these three routing protocols are based on the various protocol parameters such as Route Discovery, Network Overhead, Periodic Broadcast, Node overhead etc.